The impacts of flowering phenology on the reproductive success of the narrow endemic Nouelia insignis Franch. (Asteraceae) - FangYan Liu; ChengJie Gao; Min Chen; GuoYong Tang; Yongyu Sun; Kun Li (Ecology and Evolution, 2021)
Abstract Nouelia insignis Franch. (Asteraceae) is a short, narrow endemic and endangered tree, growing with a natural population in the dry and hot valley of the Jinsha River in the southwest area of China. In this work, flowering phenology (time and duration), floral biology, visit frequency and behavior of pollinators, and pollination characteristics were studied based on investigation in the field and analysis in the laboratory with the help of a stereomicroscope, and the relationship between seed setting rate and reproductive traits, as well as the relationship between flowering time and rainfall before flowering, was tested using the method of general linear regression model. The results showed that natural population of N. insignis exhibited high flowering synchrony with relatively stable flowering duration, and the flowering time fluctuated greatly depending on the rainfall 5 months before flowering. The pollination of N. insignis required pollinators, and insect activities played a very important role in the pollination process. However, lack of the pollinators was not a limitation for reproductive fitness in N. insignis, although the number of pollinators was small and the frequency of visits was low. In addition, no pollen limitation was found during pollination. The average seed setting rate of N. insignis in the natural condition was only 1.52%–3.73%, and it was generally affected by changes in flowering phenology between years and had a higher seed set in early flowering year. The annual variation of seed set might be related to the annual variations of stamen and pistil functions, such as changes of pollen viability and stigma receptivity, which were closely related to flowering time. The results of this study are of value for further conservation actions on natural population of this threatened endemic plant.